Implementation of Problem Solving-Based Electron Configuration E-Modules to Improve Student Learning Outcomes - Sunarya, Risa Rahmawati; Hijriansyah, Reza; Aisyah, Riri (Jurnal Pendidikan Kimia Indonesia, 2024)
This research aims to analyze the improvement in student learning outcomes in the application of the problem-solving-based electron configuration e-module. The true-experiment method with a pretest-posttest design was used in this research so that learning outcomes from the control class and the experimental class could be compared. The research results show that during the process of implementing the e-module, student activities went very well. At the stages of analyzing problems, making hypotheses, collecting data, testing hypotheses, and making conclusions respectively, students got an average score of 84.25; 82.5; 80.5; 100; and 89.5. The statistical test of student learning outcomes in the control class and experimental class using the Mann-Withney U test shows a significance value of 0.013 so it can be concluded that there is a significant difference between student learning outcomes with the application of e-modules and without the application of e-modules in learning.